Trees diversity explains variations in biodiversity-ecosystem function relationships across environmental gradients and conservation status in riparian corridors - Kinnoumè, Socrate Mercator Dossou; Gouwakinnou, Gérard Nounagnon; Noulèkoun, Florent; Balagueman, Rodrigue Ogoulonou; Houehanou, Thierry Dèhouégnon; Natta, Armand Kuyéma (Frontiers in Forests and Global Change, 2024)
Riparian ecosystems are recognized as large reservoirs of biodiversity providing important ecosystem services. However, the relationship between tree species diversity and ecosystem functions and the underlying ecological mechanisms have less been studied in riparian corridors. This study assessed the effect of plant diversity (taxonomic, functional, and phylogenetic) on riparian ecosystem functions (habitat quality – HbQ and aboveground carbon – AGC) across environmental gradients (distances to stream bed) and conservation status. Data were collected from 96 inventory plots installed in a 1 km buffer zone on either side of permanent streams in the Upper Ouémé watershed in northern Benin. We employed linear mixed effects models and structural equation modeling to analyze the data. We found that ecosystem functions (HbQ, AGC) and diversity attributes including species richness (SR), Faith's phylogenetic diversity index (PD) and community-weighted mean of maximum height (CWMHmax) were significantly lower away from the streambed than nearby. The correlation between SR and ecosystem functions was significant and positive across and within the distance gradient and conservation status. We also found that the CWMHmax was the best predictor of both ecosystem functions, and that PD mediated the effect of SR on AGC and HbQ in areas close to the streambed and in unprotected areas, respectively. Our study reveals the influence of human activities on biodiversity and ecosystem functioning relationships in riparian corridors and provides new insights into the importance of tall stature trees and species with distant lineages for the functioning of these ecosystems. Based on the variables measured and tested in this study, we argue that riparian corridor management policies should consider plant traits and phylogeny and promote wider riparian buffers for the co-benefits of biodiversity conservation and climate change mitigation.